Deficiency of HIF1α in Antigen-Presenting Cells Aggravates Atherosclerosis and Type 1 T-Helper Cell Responses in Mice. Issue 11 (November 2015) - Chaudhari, Sweena M.; Sluimer, Judith C.; Koch, Miriam; Theelen, Thomas L.; Manthey, Helga D.; Busch, Martin; Caballero-Franco, Celia; Vogel, Frederick; Cochain, Clément; Pelisek, Jaroslav; Daemen, Mat J.; Lutz, Manfred B.; et al.
Abstract : Objective—: Although immune responses drive the pathogenesis of atherosclerosis, mechanisms that control antigen-presenting cell (APC)–mediated immune activation in atherosclerosis remain elusive. We here investigated the function of hypoxia-inducible factor (HIF)-1α in APCs in atherosclerosis. Approach and Results—: We found upregulated HIF1α expression in CD11c + APCs within atherosclerotic plaques of low-density lipoprotein receptor–deficient ( Ldlr −/− ) mice. Conditional deletion of Hif1a in CD11c + APCs in high-fat diet–fed Ldlr −/− mice accelerated atherosclerotic plaque formation and increased lesional T-cell infiltrates, revealing a protective role of this transcription factor. HIF1α directly controls Signal Transducers and Activators of Transcription 3 ( Stat3 ), and a reduced STAT3 expression was found in HIF1α-deficient APCs and aortic tissue, together with an upregulated interleukin-12 expression and expansion of type 1 T-helper (Th1) cells. Overexpression of STAT3 in Hif1a -deficient APCs in bone marrow reversed enhanced atherosclerotic lesion formation and reduced Th1 cell expansion in chimeric Ldlr −/− mice. Notably, deletion of Hif1a in LysM + bone marrow cells in Ldlr −/− mice did not affect lesion formation or T-cell activation. In human atherosclerotic lesions, HIF1α, STAT3, and interleukin-12 protein were found to colocalize with APCs. Conclusions—: Our findings identify HIF1α to antagonize APC activation and Th1 T cell polarization during atherogenesis in Ldlr −/− mice and to attenuate the progression of atherosclerosis. These data substantiate the critical role of APCs in controlling immune mechanisms that drive atherosclerotic lesion development. Abstract : Supplemental Digital Content is available in the text.